2003
DOI: 10.1021/ma025862u
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Electroluminescent Property of CN−Poly(dihexylfluorenevinylene) for LEDs

Abstract: A new green electroluminescence polymer, CN-poly(dihexylfluorenevinylene) (CN-PDHFV), which denotes poly [(9,9-, was synthesized by condensation polymerization utilizing the Knoevenagel reaction. The resulting polymer exhibits good solubility in common organic solvents such as chloroform, THF, and ODCB. The polymer is also easily cast on a glass plate to green film. The UV-vis spectrum of the polymer exhibits characteristically a broad absorption band at 440 nm. This polymer shows photoluminescence around λ ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…15 It is reported that the bandgaps of the polymers were reduced by increasing the ratio of the vinylene groups to thiophene unit and incorporation of cyano group in the vinylene units. 16,17 The utilization of the cyano substituted vinylene unit coupled with DTBT moiety can provide effective electron deficient unit for the ICT.…”
Section: -6mentioning
confidence: 99%
“…15 It is reported that the bandgaps of the polymers were reduced by increasing the ratio of the vinylene groups to thiophene unit and incorporation of cyano group in the vinylene units. 16,17 The utilization of the cyano substituted vinylene unit coupled with DTBT moiety can provide effective electron deficient unit for the ICT.…”
Section: -6mentioning
confidence: 99%
“…By attentively selecting the conjugated polymer backbone and side chains, we can alter a variety of photoluminescence and electroluminescence colors. Till now PPV has been reported with a variety of substituents such as alkoxy [5], fluorenyl [6], phenyl [7], alkyl [8], cyano group [9] or halides [10]. Among these PPV conjugated polymers, alkoxy PPV conjugated polymers with poor solubility are detrimental for device elaboration.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Recently, PPVs with F atoms on the vinylene units, [27,28] that is, poly( p-phenylene difluorovinylene)s (PPDFVs), have been considered for optimizing PPV materials with blue-light emission. [29,30] The rationale for analyzing PPDFVs with fluorinated double bonds is two-fold. The presence of F atoms on double bonds has been reported [27] to increase the resistance of these polymers against double-bond photo-oxidation and to reduce the electron-injection barrier, both of which are major drawbacks to the widespread use of organic semiconductors in commercial electroluminescent devices.…”
mentioning
confidence: 99%